A Reflexive View of Refugee Integration and Inclusion: A Case Study of the Mennonite Central Committee and the Private Sponsorship of Refugees Program - Good Gingrich, Luann; Enns, Thea (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2019)
Through a qualitative case study with Mennonite Central Committee (MCC) sponsorship groups and former refugee newcomers, we adopt a reflexive, relational, and systemic lens (Bourdieu) to analyze the institutional and interpersonal relationships in the Private Sponsorship of Refugees (PSR) Program, and more specifically, the ways in which MCC Ontario’s sponsorship program invigorates or frustrates dynamics of social inclusion. We situate the institutional relations of the PSR Program as nested social fields and sub-fields, revealing complementary and competing systems of capital that direct explicit and implicit visions for “success” in MCC sponsorships. A peculiar Mennonite/MCC social field and structure of capital generates institutional and social tensions, yet an ambivalent disposition or divided habitus presents possibilities for seeing, understanding, and challenging dynamics of social exclusion.